Ujı Kualıtatıf Rhodamın B pada Saus Jajanan "Tusuk-Tusuk" dı Taman Berlabuh dan Taman Oval kota Tarakan - Agus Amanda Defi Rahayu; Jufri Ubrusun; Irma Novrianti (Journal Borneo, 2023)
The "tusuk-tusuk" snack is one of the foods loved by all groups, with a delicious taste, and is usually served with added sauce. Rhodamine B is one of the synthetic dyes used in the textile industry. Often rogue traders use Rhodamin B in food that is sold to enhance the color of the food. As is known, Rhodamin B can irritate the eyes, digestive tract, and respiratory tract. This study intends to investigate the presence or absence of the identification of the hazardous substance Rhodamine B in tomato sauce, a street food "tusuk-tusuk" circulating in the Berlabuh and Oval parks, Tarakan city. Each sauce is obtained from " tusuk-tusuk " snacks that circulate in the Berlabuh and Oval parks. The research was carried out and obtained 10 samples circulating in the Berlabuh and Oval parks then, each sample weighed as much as 25 grams, and the sample was dissolved with heated aquadest. After that, the samples were tested using the rapid test method (Rapid test kit). The results of this study indicate that out of 10 samples of the “tusuk-tusuk” snack sauce at Berlabuh and Oval Parks, Tarakan City, did not contain Rhodamin B.